Modified maleimide resin composition containing POSS structure, prepreg and copper foil substrate

By introducing bismaleimide compounds containing POSS structure and maleimide groups, a modified maleimide resin composition was prepared, which solved the shortcomings of the existing bismaleimide resin in terms of dielectric properties, peel strength and glass transition temperature, and achieved improvements in many properties such as low dielectric constant, low dielectric loss and high glass transition temperature.

CN118878749BActive Publication Date: 2025-04-04广东伊帕思新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411075309.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-04
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The existing bismaleimide resins have shortcomings in dielectric properties and peel strength, and the glass transition temperature does not meet the high requirements.

Method used

A bismaleimide compound containing a POSS structure is introduced. The POSS structure is combined with a maleimide group to prepare a modified maleimide resin composition, including bismaleimide compound with a POSS structure, polyphenylene ether and 1,2-bis(4-vinylphenyl)ethane and other components.

Benefits of technology

It achieves low dielectric constant and low dielectric loss, and has extremely high glass transition temperature, low thermal expansion coefficient, very low water absorption and good thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000009823780000011
    Figure FHA0000009823780000011
  • Figure FHA0000009823780000012
    Figure FHA0000009823780000012
  • Figure FHA0000009823780000013
    Figure FHA0000009823780000013
Patent Text Reader

Abstract

The invention discloses a modified maleimide resin composition containing a POSS structure, which comprises the following components by 100 parts by weight: 10-80 parts of bismaleimide compounds containing POSS structure, 10-60 parts of polyphenylene ether, and 5-60 parts of 1,2-bis(4-vinylphenyl)ethane. The present invention introduces a bismaleimide compound containing a POSS structure, and the introduced POSS structure cooperates with a maleimide group to ensure low dielectric constant and low dielectric loss of the composition, and the composition also has extremely high glass transition temperature, relatively low thermal expansion coefficient, very low water absorption and good thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of resin compositions, in particular to a modified maleimide resin composition containing a POSS structure, a prepreg and a copper foil substrate. Background Art

[0002] In recent years, with the rapid development of mobile internet technology and the increasing demand for mobile data, the integration and miniaturization of semiconductors used in electronic devices, communication devices, personal computers, and the like have accelerated. Consequently, the properties required of semiconductor package laminates (such as metal-clad laminates) used in printed circuit boards (PCBs) are becoming increasingly stringent.

[0003] Bismaleimide resin is a high-performance thermosetting resin matrix with active double bonds. It has been widely used in transportation, aerospace, mechanical electronics and other fields. In addition, bismaleimide resin has high heat resistance, oxidation resistance and ablation resistance. Therefore, most of the industry currently uses bismaleimide as the raw material of the substrate. Although conventional bismaleimide has a high glass transition temperature, its dielectric properties and peel strength are still lacking, and the glass transition temperature has not yet reached a high level. Therefore, it is necessary to propose a new solution to improve the above problems. Summary of the Invention

[0004] In view of this, the present invention is directed to the deficiencies in the prior art, and its main purpose is to provide a modified maleimide resin composition, a prepreg and a copper foil substrate containing a POSS structure, which introduces a bismaleimide compound containing a POSS structure, and the introduced POSS structure cooperates with the maleimide group to ensure the low dielectric constant and low dielectric loss of the composition. At the same time, the composition also has an extremely high glass transition temperature, a relatively low thermal expansion coefficient, a very low water absorption rate and good thermal stability.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A modified maleimide resin composition containing a POSS structure comprises the following components based on 100 parts by weight: 10-80 parts of a bismaleimide compound containing a POSS structure, 10-60 parts of polyphenylene ether, and 5-60 parts of 1,2-bis(4-vinylphenyl)ethane.

[0007] As a preferred embodiment, the general structural formula of the bismaleimide compound containing POSS structure is as follows:

[0008] Among them, R1 is

[0009] As a preferred embodiment, the polyphenylene ether is a polyphenylene ether containing a carbon-carbon unsaturated group, and the polyphenylene ether containing a carbon-carbon unsaturated group contains at least one of vinyl, allyl, propenyl, acrylate or methacrylate groups at one end, both ends or side chain.

[0010] As a preferred embodiment, the structural formula of the 1,2-bis(4-vinylphenyl)ethane is

[0011]

[0012] As a preferred embodiment, the invention further comprises 1-30 parts of hydrocarbon resin.

[0013] As a preferred embodiment, the hydrocarbon resin is at least one of polybutadiene, modified polybutadiene, polypentadiene, modified polypentadiene, polyisoprene, modified polyisoprene, polystyrene, butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, hydrogenated diene-butadiene-styrene copolymer, maleated diene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-divinylbenzene copolymer, maleated styrene-butadiene copolymer, cyclopentadiene, modified cyclopentadiene, dicyclopentadiene, modified dicyclopentadiene, styrene-pentadiene copolymer, styrene-polypentadiene copolymer, butadiene-cyclopentadiene copolymer, ethylene-cyclopentadiene copolymer, norbornene polymer, and modified norbornene polymer.

[0014] A prepreg is prepared from the aforementioned modified maleimide resin composition containing a POSS structure.

[0015] A copper foil substrate is prepared from the aforementioned prepreg.

[0016] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0017] The present invention introduces a bismaleimide compound containing a POSS structure. The introduced POSS structure cooperates with the maleimide group to ensure a low dielectric constant and low dielectric loss of the composition. At the same time, the composition also has an extremely high glass transition temperature, a low thermal expansion coefficient, very low water absorption and good thermal stability.

[0018] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below with reference to specific embodiments. DETAILED DESCRIPTION

[0019] The invention discloses a modified maleimide resin composition containing a POSS structure. The modified maleimide resin composition comprises the following components based on 100 parts by weight: 10-80 parts of a bismaleimide compound containing a POSS structure, 10-60 parts of polyphenylene ether, and 5-60 parts of 1,2-bis(4-vinylphenyl)ethane.

[0020] The general structural formula of the bismaleimide compound containing POSS structure is as follows:

[0021] Among them, R1 is

[0022] The polyphenylene ether is a polyphenylene ether containing a carbon-carbon unsaturated group, and one end, both ends or a side chain of the polyphenylene ether containing a carbon-carbon unsaturated group contains at least one group selected from vinyl, allyl, propenyl, acrylate or methacrylate.

[0023] The structural formula of the 1,2-bis(4-vinylphenyl)ethane is

[0024]

[0025] And, further comprising 1-30 parts of a hydrocarbon resin, wherein the hydrocarbon resin is at least one of polybutadiene, modified polybutadiene, polypentadiene, modified polypentadiene, polyisoprene, modified polyisoprene, polystyrene, butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, hydrogenated diene-butadiene-styrene copolymer, maleic anhydride diene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-divinylbenzene copolymer, maleic anhydride styrene-butadiene copolymer, cyclopentadiene, modified cyclopentadiene, dicyclopentadiene, modified dicyclopentadiene, styrene-pentadiene copolymer, styrene-polypentadiene copolymer, butadiene-cyclopentadiene copolymer, ethylene-cyclopentadiene copolymer, norbornene polymer, and modified norbornene polymer.

[0026] The present invention also discloses a prepreg, which is prepared from the modified maleimide resin composition containing the POSS structure. The preparation process is as follows: first, the above-mentioned raw material components are mixed with a filler and a catalyst according to the components, and the mixture is uniformly mixed by stirring to obtain the modified maleimide resin composition containing the POSS structure; then, the modified bismaleimide resin composition is placed in an appropriate amount of butanone solvent, and the mixture is uniformly mixed by stirring to obtain a glue solution with a solid weight percentage of 65%; the glue solution is impregnated and coated on an E glass fiber cloth with a model number of 7628, and the cloth is dried in a 160°C oven for 5 minutes to obtain the prepreg.

[0027] The present invention also discloses a copper foil substrate made from the aforementioned prepreg. The manufacturing process is as follows: a sheet of 18-μm-thick copper foil is placed on each of the upper and lower surfaces of the prepreg. The prepreg is then placed in a vacuum hot press and pressed for 4 hours at a pressure of 1.5 MPa and a temperature of 180-220°C to produce a laminate. This manufacturing method is employed in all subsequent examples.

[0028] The raw materials used in the following examples and comparative examples are shown in Table 1:

[0029]

[0030]

[0031] Table 1

[0032] The preparation method of BMI-P is as follows:

[0033] At first, under the atmosphere of nitrogen, 1.903g (11.2mmol) silicon chloride and 3.572g (35.3mmol) triethylamine are dissolved among the 20ml THF, obtain the mixing THF solution of silicon chloride and triethylamine, again the mixing THF solution of the silicon chloride that obtains and triethylamine is added drop-wise in the 70ml THF solution that contains 9.965g (10.7mmol) heptaphenyltrisilanol-POSS (Xi'an Qiyue biology), at room temperature stirring is spent the night, suspension is filtered, obtain Ph7The mixed solids of CI-POSS and triethylamine hydrochloride and it is dissolved in the mixed solvent of 20ml, this mixed solvent is made up of 5ml THF and 15ml chloroform, then uses 15ml water and 2ml hydrochloric acid hydrolysis 90min;

[0034] Then, the aqueous layer was removed, the mixture was extracted twice with chloroform, the organic layers were combined, and the mixture was extracted with water, dilute hydrochloric acid, water and saturated sodium chloride solution in sequence, dried over magnesium sulfate, filtered, and most of the solvent was removed. The mixture was precipitated in methanol, filtered, and dried under vacuum at 40° C. overnight to obtain 9.37 g of Ph7OH-POSS with a purity of 90%. Then, 1.701 g (3.08 mmol) of di(N-trimethylsilyl)-2-phenylamino-4,4′-chloromethylsilane and 0.314 g (3.1 mmol) of triethylamine were dissolved in water and the mixture was stirred for 2 hours. The product was dissolved in 5 ml of ether to obtain a mixed solution of di(N-trimethylsilyl)-2-phenylamino-4,4'-chloromethylsilane and triethylamine, which was then added dropwise to 17 ml of a solution containing 2.92 g (3.00 mmol) of Ph7OH-POSS in a solvent of 15 ml of ether and 2 ml of THF. The mixture was stirred at room temperature overnight, and after filtering off the triethylamine hydrochloride and removing most of the solvent, 50 ml of acidified methanol was added, stirred for 1 hour, filtered, and dried in vacuo at 60°C to obtain phenylmonosilyloxymethyldiphenylamine.

[0035] Then, 14.78 g of maleic anhydride was dissolved in 80 ml of acetone, cooled to below 20° C., and added to 80 ml of an acetone solution containing 15 g of phenylmonosilyloxymethyldiphenylamine. The reaction was carried out below 20° C. The amic acid I generated by the reaction was filtered out, washed with acetone, and dried at 60-70° C.;

[0036] Finally, 18 g of amidic acid I, 16 g of acetic anhydride, 0.09 g of nickel acetate, and 3.43 g of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and heated to 65-73° C. and stirred for 1 h. The product was filtered and the generated water was evaporated. The product was then added to 30 ml of methanol, the precipitate was filtered, and the precipitate was washed with 50% aqueous methanol, 20% aqueous methanol, and water, and then recrystallized from methanol and dried at 70-100° C., with an mp of 155-157° C., to obtain the product BMI-P.

[0037] The preparation process of BMI-P is as follows:

[0038]

[0039]

[0040] The raw material ratios of Examples 1-6 and Comparative Examples 1-7 are shown in Table 2:

[0041] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 BMI-P 60 45 70 10 20 35 BMI-1000 70 BMI-7000 60 70 BMI-2000 60 70 BMI-4000 60 70 SA90000 20 35 10 70 60 45 20 20 20 35 35 10 10 Ricon100 15 15 15 15 15 15 15 15 15 15 15 15 15 BVPE 5 5 5 5 5 5 5 5 5 5 5 5 5 DCP 2 2 2 2 2 2 2 2 2 2 2 2 2 SC-2050-KC 255 255 255 255 255 255 255 255 255 255 255 255 255

[0042] Table 2

[0043] The above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 3:

[0044] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Dielectric constant SFDR(10G) 3.3 3.32 3.26 3.55 3.43 3.39 3.64 3.5 3.42 3.42 3.43 3.52 3.48 Dielectric loss SPDR(10G) 0.002 0.0026 0.0018 0.0035 0.0033 0.003 0.0036 0.0039 0.0033 0.0035 0.0038 0.0035 0.0028 Glass transition temperature ℃ 278 262 295 237 238 246 237 253 242 253 245 258 246 Water absorption % 0.18 0.20 0.12 0.32 0.25 0.22 0.23 0.24 0.23 0.25 0.28 0.32 0.37 X / Y axis CTE ppm / ℃ 8 11 7 15 13 13 11 10 12 12 11 12 12 Peel strength N / mm 0.72 0.6 0.75 0.4 0.42 0.56 0.52 0.51 0.52 0.45 0.45 0.41 0.51

[0045] Table 3

[0046] Analysis of the above data shows that Example 1 and Comparative Examples 1-3 use the same proportion of raw materials. The difference is that Example 1 uses a homemade bismaleimide compound BMI-P, while Comparative Examples 1-3 use common commercially available bismaleimide resins. The finished product prepared in Example 1 is significantly superior to the finished products prepared in Comparative Examples 1-3 in terms of dielectric constant, dielectric loss, glass transition temperature, peel strength, water absorption, and thermal expansion coefficient. The glass transition temperature can be increased by up to 41°C, and the dielectric loss is reduced by nearly half.

[0047] At the same time, compared with Comparative Examples 4 and 5, the finished product prepared in Example 2 is superior to the finished products prepared in Comparative Examples 4 and 5 in terms of dielectric constant, dielectric loss, glass transition temperature, peel strength, water absorption and thermal expansion coefficient. Compared with Example 1 and Example 2, the ratio of bismaleimide compound to polyphenylene ether in Example 2 is smaller, and the dielectric constant, peel strength and water absorption of the two are roughly the same, but the finished product prepared in Example 2 is slightly worse than that prepared in Example 1 in terms of glass transition temperature, dielectric loss and thermal expansion coefficient. The finished products of Comparative Examples 4 and 5 are shown in Table 1. Compared with Comparative Examples 1-3, the ratio of the bismaleimide compound to the polyphenylene ether in Comparative Examples 4 and 5 is smaller. However, the finished products obtained have substantially the same performance as those in Comparative Examples 1-3. When the ratio of the bismaleimide compound to the polyphenylene ether is reduced, different results are obtained by selecting different bismaleimide compounds. It can be seen that the role of the BMI-P in the reaction system of the present invention is completely different from that of the commercially available bismaleimide in the reaction system.

[0048] In addition, the finished product prepared in Example 3 is the best in terms of dielectric constant, dielectric loss, glass transition temperature, peel strength, water absorption and thermal expansion coefficient. Compared with Comparative Examples 6 and 7, Example 3 uses the same proportion of raw materials, but uses a different bismaleimide compound. The finished product prepared in Example 3 is significantly superior to the finished products prepared in Comparative Examples 6 and 7 in terms of dielectric constant, dielectric loss, glass transition temperature, peel strength, water absorption and thermal expansion coefficient. The glass transition temperature can be increased by up to 49°C, and the dielectric loss is reduced by nearly half.

[0049] And, from the perspective of Examples 1-6, the performance of the finished products obtained in Examples 1-6 is affected by the ratio of the bismaleimide compound to the polyphenylene ether, while in Comparative Examples 1-7, the performance of the finished products obtained in Comparative Examples 1-7 is roughly the same and is not affected by the ratio of the bismaleimide compound to the polyphenylene ether. It can be seen that the bismaleimide compound selected by the present invention, after the POSS structure is introduced, the POSS structure and the maleimide group are used in combination, which produces a very positive effect and further optimizes the performance of the finished product finally obtained.

[0050] The above description is merely a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any minor modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A modified maleimide resin composition containing a POSS structure, characterized in that: The composition comprises the following components based on 100 parts by weight: 10-80 parts of a modified bismaleimide compound containing a POSS structure, 10-60 parts of polyphenylene ether, and 5-60 parts of 1,2-bis(4-vinylphenyl)ethane; the general structural formula of the bismaleimide compound containing a POSS structure is as follows: Among them, R1 is The polyphenylene ether is a polyphenylene ether containing carbon-carbon unsaturated groups, and one end, two ends or a side chain of the polyphenylene ether containing carbon-carbon unsaturated groups contains at least any one of vinyl, allyl, propenyl, acrylate or methacrylate groups.

2. The modified maleimide resin composition containing POSS structure according to claim 1, wherein: The structural formula of the 1,2-bis(4-vinylphenyl)ethane is 3. The modified maleimide resin composition containing POSS structure according to claim 1, characterized in that: The invention further comprises 1-30 parts of hydrocarbon resin.

4. The modified maleimide resin composition containing POSS structure according to claim 3, characterized in that: The hydrocarbon resin is at least one of polybutadiene, modified polybutadiene, polypentadiene, modified polypentadiene, polyisoprene, modified polyisoprene, polystyrene, butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, hydrogenated diene-butadiene-styrene copolymer, maleic anhydride diene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-divinylbenzene copolymer, maleic anhydride styrene-butadiene copolymer, styrene-pentadiene copolymer, butadiene-cyclopentadiene copolymer, ethylene-cyclopentadiene copolymer, norbornene polymer, and modified norbornene polymer.

5. A prepreg, characterized in that: The invention is prepared from the modified maleimide resin composition containing POSS structure as described in any one of claims 1 to 4.

6. A copper foil substrate, characterized in that: Prepared from the prepreg according to claim 5.

Citation Information

Patent Citations

  • Maleimide with cage-type silsesquioxane structure and synthesis method thereof

    CN101723968A

  • Modified maleimide resin composition and prepreg and laminate prepared therefrom

    CN109054381A